A STUDY ON THE SPATIAL DIFFERENTIATION OF THE SOCIO-ECONOMIC AND TOURIST SITUATION OF SELECTED MUNICIPALITIES OF THE WEST POMERANIAN VOIVODESHIP - Brelik, Agnieszka; Oleszczyk, Natalia (Acta Scientiarum Polonorum. Oeconomia, 2023)
Aim: The aim of the article was to develop an original classification of municipalities in the West Pomeranian Voivodeship, Poland, with particular emphasis on measuring local development, taking into account the development of health tourism. Methods: The research procedure consisted of the following stages: collection of data and assessment of their completeness for the West Pomeranian region, calculating the values of the indicators, constructing rankings of municipalities in a one-dimensional space of characteristics-indicators and distinguishing typological groups of municipalities similar in terms of the degree of development of the socio-economic and tourist situation. The classification of sub-regions was carried out using discriminant analysis. For this purpose, the indicators characterizing the socio-economic and tourist situation in the selected West Pomeranian Voivodeship municipalities were used, taking into account the division into municipalities: urban (1), rural (2), and urban-rural (3). The preliminary classification of the objects into groups, and thus the selection of the grouping variable, was carried out using the k-means method. The study used secondary data from the Local Data Base – GUS. Results: As a result of the survey, the analyzed local government units were divided into three groups. However, the presented results of the classification do not indicate the dependence of the improvement of socio-economic characteristics on the provision of tourism services in the municipality (including health tourism). Conclusions: Empirical studies show that the placement of municipalities in the West Pomeranian Voivodeship reveals clear relationships between the territorial distribution of health tourism units and the territorial distribution of natural assets and access to the Baltic Sea.